Validation of a wireless head acceleration measurement system for use in soccer play - Hanlon, E.; Bir, C. (Journal of Applied Biomechanics, 2010)
Soccer heading has been studied previously with conflicting results. One major issue is the lack of knowledge regarding what actually occurs biomechanically during soccer heading impacts. The purpose of the current study is to validate a wireless head acceleration measurement system, head impact telemetry system (HITS) that can be used to collect head accelerations during soccer play. The HIT system was fitted to a Hybrid III (HIII) head form that was instrumented with a 3-2-2-2 accelerometer setup. Fifteen impact conditions were tested to simulate impacts commonly experienced during soccer play. Linear and angular acceleration were calculated for both systems and compared. Root mean square (RMS) error and cross correlations were also calculated and compared for both systems. Cross correlation values were very strong with r = .95 ± 0.02 for ball to head forehead impacts and r = .96 ± 0.02 for head to head forehead impacts. The systems showed a strong relationship when comparing RMS error, linear head acceleration, angular head acceleration, and the cross correlation values.